1996
DOI: 10.1002/(sici)1096-987x(19961130)17:15<1757::aid-jcc6>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rigid and flexible simple point charge water models at supercritical conditions

Abstract: This study investigates the differences between the predictions of various properties of rigid and flexible simple point charge water models at supercritical conditions. Molecular dynamics simulations were conducted for supercritical water in a temperature range of 773-1073 K and densities in the range 115-659 kg/m3. We present thermodynamic data, pair correlation functions, selfdiffusivity, power spectra, dielectric constants, and variaous measures of hydrogen bonding at different state conditions. The flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…MD simulations with periodic boundary conditions (PBC) were performed by using Gromacs suite of programs (Version 4.6.5) 58 . A combination of CLAYFF force field (parameters given in Table S1 ) 59 and simple-point-charge (SPC) water model 60 was used. Recently, the CLAYFF force field has achieved unprecedented success in modeling clay minerals, and the conjunction with SPC water model has been demonstrated to be accurate to simulate hydrated minerals and aqueous-mineral interfaces 14 23 27 61 62 63 64 65 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…MD simulations with periodic boundary conditions (PBC) were performed by using Gromacs suite of programs (Version 4.6.5) 58 . A combination of CLAYFF force field (parameters given in Table S1 ) 59 and simple-point-charge (SPC) water model 60 was used. Recently, the CLAYFF force field has achieved unprecedented success in modeling clay minerals, and the conjunction with SPC water model has been demonstrated to be accurate to simulate hydrated minerals and aqueous-mineral interfaces 14 23 27 61 62 63 64 65 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…This time is also identified as mean HB persistence time, or a continuous survival time constant. 19 What is the relation between P(t) and p(t)? For the moment we restrict ourselves to the Markovian process, where the future of the hydrogen bond population operator, h(t), depends only on its present state, not on its past.…”
Section: A Continuum World: Probability Densities Of First Passage Tmentioning
confidence: 99%
“…This leads to much longer lifetimes than obtained in case ͑1͒. Since this first, yet elaborate attempt to understand H bond dynamics in water almost 20 years ago 16 other authors have typically focused on either of these methods using a particular potential and definition for a bond to estimate HB lifetimes in several systems: ambient water, 18 pure supercritical water, [19][20][21] solvation in supercritical water, 22 pure methanol, 14 pure ethanol, 23 water near hydrogels, 24 by assuming a ''quasiexponential'' decay of calculated correlations functions.…”
Section: Introductionmentioning
confidence: 99%
“…The high N b result and longer average bond lifetimes could be due to hydrogen bond flexibility, which does not require reorientation for bond formation. Mizan et al[49] investigated the benefits of flexibility in a simple point charge water model by comparing a flexible model of SPC proposed by Teleman et al[50] (TEL) with the original rigid model SPC[28] and reported TEL exhibited a greater degree of hydrogen bonding and more persistent hydrogen bonds at supercritical conditions.…”
Section: Resultsmentioning
confidence: 99%